2021
DOI: 10.3389/fendo.2021.653184
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance and Management of Recurrent Laryngeal Nerve Inlet Zone Lymph Nodes Metastasis in Papillary Thyroid Cancer

Abstract: BackgroundRecurrent nodal disease often occurs in recurrent laryngeal nerve inlet zone (RLNIZ), leading to difficult surgical management.MethodsMedical records of 947 patients with PTC and 33 patients with recurrent PTC were retrospectively reviewed. Totally 169 sides of RLNIZ dissection in 152 patients (17 cases were bilateral and 135 cases were unilateral) with primary surgery and 4 patients with structural recurrent disease were included for the analysis.ResultsThe rate of lymph node metastasis in RLNIZ was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similar to the results of Zheng and cols. (28), more evidence is needed to support the correlation between the vertical location of the tumor and RLN invasion in current study; while RLN invasion was much commonly presented in cases where tumor located on the dorsal side of thyroid gland as compared to those on the ventral side, which indicated that features of posterior tumor should be given more attentions to the possibility of RLN invasion, even in the absence of VCP (29).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar to the results of Zheng and cols. (28), more evidence is needed to support the correlation between the vertical location of the tumor and RLN invasion in current study; while RLN invasion was much commonly presented in cases where tumor located on the dorsal side of thyroid gland as compared to those on the ventral side, which indicated that features of posterior tumor should be given more attentions to the possibility of RLN invasion, even in the absence of VCP (29).…”
Section: Discussionmentioning
confidence: 66%
“…In addition to extrathyroidal extension, some cases in this study exhibited other aggressive behaviors, for example LNM ( 33 ). The LNM in thyroid cancer often occurs in the central neck, so that RLN could also be infiltrated ( 28 ). More importantly, a fair number of patients suffered asymptomatic RLN invasion by LNM until detected in thyroid surgery ( 8 ).…”
Section: Discussionmentioning
confidence: 99%